The level of Psychological flexibility among students of the College of Education in the light of some variables A field study at Tartous University (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to identify the level of psychological flexibility among students of the Faculty of Education at Tartous University, and to identify the differences in the level of psychological flexibility within four areas (insight - creativity - forming relationships - balance) among the members of the research sample according to the difference of each of the sex, and the school year (first - fourth). The research sample consisted of (412) male and female students from the Faculty of Education at Tartous University during the first semester of the year (2019/2020). To achieve the objectives of the research, the researcher built a scale of (25) phrases to measure psychological flexibility in its four domains, after verifying its validity and stability. The appropriate barometric statistical methods were used - after checking the moderation of the distribution - represented by the arithmetic mean, standard deviation, t-test for two independent groups, and Mann-Whitney test, and the results showed the following:- There is a high level of psychological flexibility among the members of the research sample, with a mean of (3.6).- There are statistically significant differences in the level of psychological flexibility among the members of the research sample due to the variable of the school year, and in favor of first-year students.- There are no statistically significant differences in the level of psychological flexibility among the members of the research sample due to the gender variable.